A comparison of the femoral and radial crossover techniques for vascular access management in transcatheter aortic valve implantation: The milan experience. Issue 1 (24th August 2013) - Curran, Helen; Chieffo, Alaide; Buchanan, Gill Louise; Bernelli, Chiara; Montorfano, Matteo; Maisano, Francesco; Latib, Azeem; Maccagni, Davide; Carlino, Mauro; Figini, Filippo; Cioni, Micaela; Canna, Giovanni La; et al.
<x xml:space="preserve">Abstract</x> Objective To compare radial and femoral crossover techniques (CT) for vascular access management in transcatheter aortic valve implantation (TAVI). Background Femoral crossover for controlled angiography and balloon inflation of the therapeutic access site to facilitate safe vascular closure is beneficial but technically challenging in patients with complex femoral anatomy. An alternative approach should be available. Methods Between June 2011 and March 2012, 41 transfemoral TAVI patients receiving the femoral CT were compared to 46 transfemoral TAVI patients receiving the radial CT. Outcomes were 30‐day valve academic research consortium (VARC) endpoints. Results Patients undergoing the radial CT received higher median contrast volumes (150 interquartile range [IQR]: 105–180 vs. 111 IQR: 90–139 ml; P = 0.025) but procedural radiation dose and fluoroscopy times were comparable. Thirty day all cause and cardiovascular death were similar between radial and femoral CT groups (respectively 2.4% vs. 7.9%, P = 0.258 and 0% vs. 7.9%, P = 0.063). There were no differences in major vascular complications (4.3% vs. 7.3%, P = 0.553), life threatening or major bleeding events (respectively 9.1% vs. 19.5%, P = 0.168 and 13.6% vs. 22%, P = 0.315). Conclusion In TAVI cases with unfavorable contralateral femoral anatomy, radial CT for vascular access management is a reasonable alternative to the femoral CT. © 2013 Wiley Periodicals, Inc.